Flood Mitigation in East Coast Semarang City: Hydrological and Hydraulic Analysis for Polder System Optimization - Ikhwanudin; Imadudin Harjanto; Risdiana Cholifatul Afifah; Farida Yudaningrum (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Flooding is a recurring hazard across Indonesia, particularly in urban regions such as Semarang City, where high-intensity rainfall, tidal surges, land subsidence, and changes in land use contribute to frequent inundation. This study investigates the effectiveness of the Sringin Polder system in mitigating flood risks through an integrated hydrological and hydraulic analysis. The hydrological component involved calculating design rainfall values for various return periods, with a peak intensity of 113 mm recorded for the 10-year event. These values were used to simulate flood discharges using HEC-RAS.For the 25-year return period, the main river channel produced a simulated flood discharge of 47.42 m³/s, resulting in water overtopping the left embankment by 0.545 m at station P.30. calculated flood flow and the existing capacity of the river cross-sections.